Pengaruh Iklim Organisasi Terhadap Kinerja Pegawai Negeri Sipil Pada Kantor Kecamatan Bola Kabupaten Wajo - Asmanurhidayani, Asmanurhidayani; Darwis Darwis; Satriani Satriani (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
This research is based on the idea that every organization, both government and private, has goals to be achieved. Where the cooperation of leaders and those who are led can carry out tasks and functions within the structure of the existing organizational environment. Human resource management requires open communication and relationships within the limits of authority and responsibility of each existing employee, so that the influence of Organizational Climate on employee performance provides goals and benefits for the benefit of the organization. The population of this study were all civil servants in the Bola District Office, Wajo Regency, totaling 13 people. Data collection was carried out using a questionnaire while the data analysis technique was carried out using a quantitative descriptive analysis approach. The results showed that the score obtained from Organizational Climate at the Bola District Office, Wajo Regency was in good criteria. The performance of Civil Servants at the Bola District Office, Wajo Regency, is in good criteria. Organizational Climate at the Bola District Office, Wajo Regency, is positively related to employee performance and the relationship is quite strong.